2007
DOI: 10.1309/urpqc0kye97wg111
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline Globules (Thanatosomes) in Gastrointestinal Epithelium

Abstract: Hyaline globules (HGs; thanatosomes) are well-defined morphologic and functional entities representing a degenerative phenomenon common to all cell types. We present the first quantitative and qualitative study of HGs in normal and pathologic gastrointestinal (GI) epithelium from a series of 2,230 biopsies. HGs were very rarely found in normal epithelium (1.1%), but their number increased significantly in specimens with ischemic injury (47%) and benign regenerative proliferation (70%). Their incidence in adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…In that study, progressive activation of autophagy accompanied the progression of lesions through stages of increasing malignancy. In colon cancer also, activation of the autophagy pathway is a feature of the neoplastic phenotype, both in polyps and cancers (36).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, progressive activation of autophagy accompanied the progression of lesions through stages of increasing malignancy. In colon cancer also, activation of the autophagy pathway is a feature of the neoplastic phenotype, both in polyps and cancers (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, the parasite burden consisted of scattered inconspicuous clusters of inhabited epithelium; less commonly, there was patchy or moderately diffuse involvement of the epithelium. One potential histologic mimic, hyaline globules (also known as thanatasomes), 32 can be distinguished by the presence of epithelial injury with attendant inflammation, lack of a distinct vacuole, and consistent negative staining by Alcian blue ( Image 1 ). 32 …”
Section: Resultsmentioning
confidence: 99%
“…One potential histologic mimic, hyaline globules (also known as thanatasomes), 32 can be distinguished by the presence of epithelial injury with attendant inflammation, lack of a distinct vacuole, and consistent negative staining by Alcian blue ( Image 1 ). 32 …”
Section: Resultsmentioning
confidence: 99%
“…EHGs were very rarely found in normal epithelium (1.1%), but their number increased significantly in specimens with ischemic injury (47%) and benign regenerative proliferation (70%). They concluded that Thanatosomes represented a relatively constant and useful histologic marker of enhanced cell turnover and ischemic injury [47]. Thanatosomes had been dubbed as “Death Bodies” in a report on 2 cases of malignant phylloides tumor, both of which showed numerous Thanatosomes, to the point of dominating the histological appearance and masking the stromal element [48].…”
Section: Discussionmentioning
confidence: 99%